SYSTEMATIC REVIEW : PENTINGNYA PENGEMBANGAN LIFE SKILL BAGI MAHASISWA 2020-2024 - Damaruci; Sawitri, Ina; Purnamasari, Pupung (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
This article is a systematic review examining the implementation and impact of life skills development among Indonesian university students during the 2020–2024 period. It highlights the importance of life skills development for students, referring to the WHO framework that identifies ten core life skills. These skills are categorized into five major groups based on four types of human intelligence (IQ, EQ, SQ, AQ): self-awareness and empathy, critical and creative thinking, decision-making and problem-solving, effective communication and interpersonal skills, as well as stress and emotional management. The review of 19 research articles reveals that many graduates face challenges in transitioning to the professional world, often due to an inability to master life skills. Research indicates that integrating life skills education through experiential methods, such as Project-Based Learning, can enhance students' adaptability to the dynamics of the professional world, enabling them to face career challenges with confidence and effectiveness. Key recommendations from this review include expanding project-based and experiential learning to make it more applicable and relevant to real-world contexts, as well as designing specific interventions for stress management and emotional regulation to support students' transition into the workforce. Strengthening collaboration between educators and practitioners is essential to ensure the relevance of life skills development to industry demands and real-life challenges. Furthermore, long-term research is needed to evaluate the impact of life skills programs on students' career readiness and overall well-being.